Aplicação do Modelo Transteórico de Mudança de Comportamento para o estudo do comportamento informacional de usuários de informação financeira pessoal - Matta, Rodrigo Octávio Beton [UNESP] (2012)
This study aimed to understand the information behavior of users of personal financial information based on the Transtheoretical Model of Behavior Change. The Transtheoretical Model of Behavior Change proposed by Prochaska, Norcross and DiClemente (1994) sets out the stages to be overcome by a person in a process of behavioral change. These stages are namely: pre-contemplation, contemplation, preparation, action and maintenance. The overall objective was to verify the applicability of the concepts of this model to study the information behavior of users of information. The specifics objectives of this proposed research are: a) identify and classify the users of personal financial information about the stages of change of the Transtheoretical Model of Behavior Change; b) identify characteristics of information behavior of users who are common to the stages of behavior change c) identify characteristics of information behavior of users who are specifics of each stage of behavior change and d) to systematize the data collected in the previous steps and describe the information behavior of users of personal financial information from the perspective of Transtheoretical Model of Behavior Change. A non-probabilistic sample of 850 individuals was studied using the questionnaire as a tool for data collection. Data analysis was done by applying descriptive statistics, chi-square test and non-parametric Kruskal-Wallis with Nemenyi´s comparisons. Specific algorithm was created aiming at the identification and classification of users within the stages of behavioral change. As a result it was found that the information behavior of users of... (Complete abstract click electronic access below)